A PROPOSAL ON EFFICIENCY MEASURING OF RICE MILLING PROCESS BY USING AHP / DEA METHOD - Ratna Ekawati (Journal of Engineering and Management in Industrial System, 2019)
Indonesia is a country which becomes the third largest producer of rice in the world. However, Indonesia still carries out rice importing and the rice is classified high-priced. One of the factors causing those problems is the lack of efficiency of rice milling process. Pandeglang Regency is a region which has the largest rice field in Banten. As the largest agricultural territory and a qualified rice producer, it must be possible to have rice-milling means. The rice-milling process does not always produce a constant output amounts, it can be increased or decreased, despite the use of a constant input amounts. Thus, efficiency measuring of rice-milling process is needed to find out the output increase or input decrease used in rice-milling process in order to reach an efficient point. Method applied in measuring the efficiency is AHP/DEA method. Based on acquired research results, the efficiency level at the research location was 90.01% in which from 11 rice-milling processes there was one inefficient rice-milling process which was the C rice-milling process.Keyword: AHP/DEA; efficiency; inefficiency; rice milling process.